6u=(3)

Simple and best practice solution for 6u=(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6u=(3) equation:



6u=(3)
We move all terms to the left:
6u-((3))=0
determiningTheFunctionDomain 6u-3=0
We move all terms containing u to the left, all other terms to the right
6u=3
u=3/6
u=1/2

See similar equations:

| -165.836=-10.9k | | 112m=650+88m | | 21x-7=2+18× | | 8x-3=22x+3 | | (2x5)x3=x | | 100.48=3.14*r^2*r+2/3 | | (2x5)x3=x(5x) | | 1/4(n+7)=5n−7n+1 | | 88x=26+76x-2 | | 2x+1.1=0.9 | | 14(n+7)=5n−7n+1 | | b7/8=2.15. | | (2x+7)+(5x-3)=180 | | 6(z+3)-2z=34 | | 2m–7=5 | | 5(5x+4)=145 | | 15y+38+17y-4=180 | | -4.8(6/3x-4.18)=58.56 | | 7x=9=9x-7 | | 11x-3=9x13 | | 2x–9=-3 | | −1/2d+5/8=3/8d−11/16. | | 19−8y6=5y | | 176=3x+11x+8 | | (5x-18)+(2x+10)+90=180 | | 3/4(2x+1)=5 | | F(-7)=-4x-7 | | 4d+1/3=28 | | 4x/3+6=x+2 | | 8+4n=-61+3n | | 10x+10.5+2.8=8.5+6x-15 | | 39=17x-80 |

Equations solver categories